A study on factors that influence the acceptance of online banking transaction among the government servant in Shah Alam, Selangor / Ade Irma Sukir … [et al.] - Sukir, Ade Irma; Mohsin, Basyir; Linggi @ Martin, Cynthia; Salamon, Mohd Shahrul Razi (2009)
The explosion of Internet usage and the huge funding initiatives in electronic banking have drawn the attention of researchers towards online banking. In the past, the conventional focus of online banking research has been on technological development, but this is now shifting to user-focused research. The purpose of this research is to identify the factors that influence the acceptance of online banking by the users and to identify the most common transaction by using online banking services. According to the technology acceptance model (TAM), perceived ease of use and perceived usefulness constructs are believed to be fundamental in determining the acceptance and use of various information technologies (IT). Sixty questionnaires were distributed by hand to five selected government departments in Shah Alam. Out of the sixty questionnaires distributed, only fifty questionnaires were valid. During the second visit, we gave another ten questionnaires by hand as to get sixty valid questionnaires. The research findings show that the most factors influenced the acceptance of online banking transaction among the respondents was Online Banking Website Information. The respondents were strongly agree that clear and comprehensible instructions in the website were important and influenced their acceptances of using the online banking services. Besides, the findings show that the most common transactions used by the respondents were to check balance their account balance. Pay bills and fund transfer were the next two popular transactions used by the respondents. As in the conclusion, it reveals the results of the findings that include the analysis of the demographic background, factors and the most common transactions used while the recommendation of this study made based on several logical factors and impact of current situation to the acceptance of the respondents towards the online banking services.